2021
DOI: 10.1111/1750-3841.15587
|View full text |Cite
|
Sign up to set email alerts
|

Process and product characteristics of refractance window dried Curcuma longa

Abstract: This work addresses the optimality of hot water bath based refractance window drying (RWD) characteristics of 1 mm Curcuma longa (turmeric) slices. Mylar film thickness (125 to 350 µm) and water bath temperature (65 to 95 °C) have been considered as independent variables to evaluate drying kinetics and nutritional characteristics of the process product combination. Equilibrium drying time, moisture diffusivity, fitness of thin layer models, moisture content, total phenolic content, total flavonoids content, cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Also, drying D. kotschyi by RWD and RWD+ IRD increased the TFC. Talukdar and Uppaluri (2021) reported that the turmeric dried by RWD at 95°C had the maximum TFC. Since the high temperature of the RWD reduced the drying time, the samples were exposed to heat for a shorter time, and consequently, retained heat‐sensitive constituents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, drying D. kotschyi by RWD and RWD+ IRD increased the TFC. Talukdar and Uppaluri (2021) reported that the turmeric dried by RWD at 95°C had the maximum TFC. Since the high temperature of the RWD reduced the drying time, the samples were exposed to heat for a shorter time, and consequently, retained heat‐sensitive constituents.…”
Section: Resultsmentioning
confidence: 99%
“…Since the high temperature of the RWD reduced the drying time, the samples were exposed to heat for a shorter time, and consequently, retained heat‐sensitive constituents. Due to the fast drying time, the cellular integrity is not compromised, and the TFC in the cell structure is not oxidized but preserved (Hernández‐Santos et al, 2016; Talukdar & Uppaluri, 2021). The TFC in dried apples by RWD and RWD+ IRD was higher than in the hot‐air dryer.…”
Section: Resultsmentioning
confidence: 99%
“…In the study it was determined that the activation energy values of dried peppers in RWD were lower than the other methods, therefore less energy was required for drying (Doymaz and İsmail, 2010). In the literature, the Ea values were calculated as 49.43-52.57kJ/mol for turmeric (Talukdar et al, 2021) and 41.3-31.1 kJ/mol for goldenberry (Puente -Diaz et al, 2020) in RWD, 43.9kJ/mol for dried pumpkin in FBD (Mujaffar and Ramsumair, 2019) and 47.10 kJ/mol for green pepper (Faustino et al, 2007) in CD. The findings agree with the literature.…”
Section: Resultsmentioning
confidence: 99%